2005
DOI: 10.1089/pho.2005.23.561
|View full text |Cite
|
Sign up to set email alerts
|

XeCl Excimer Laser Ablation of Rabbit Tibia Bone: Morphology of the Irradiated Site and Self-Limiting Effect

Abstract: In the present study, the laser used showed a self-limiting characteristic, which is a phenomenon that can be of great value in preserving important structures close to the working area, giving a margin of safety to the surgeon, in case of over-irradiation. This self-limiting effect is attributed to liquid filling the cavity by the bleeding and irrigation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this regard, non‐contact, blood‐, and vibration‐reduced laser surgery with free choice of cut geometry and the prevention of massive bone mill and metal abrasion would be preferable 11. Although a variety of different laser wavelengths have been experimentally analysed and suggested for cutting cortical bone 12–14, clinical laser bone ablation has thus far been rejected due to two major reasons: (i) severe collateral thermal damage and residual char formation of adjacent tissues; (ii) distinct time expenditure have strictly limited the use of different laser systems 15. Yet, in the wake of continuous developments in laser technology and an enhanced understanding of laser–tissue interaction, a re‐evaluation of laser osteotomy may be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, non‐contact, blood‐, and vibration‐reduced laser surgery with free choice of cut geometry and the prevention of massive bone mill and metal abrasion would be preferable 11. Although a variety of different laser wavelengths have been experimentally analysed and suggested for cutting cortical bone 12–14, clinical laser bone ablation has thus far been rejected due to two major reasons: (i) severe collateral thermal damage and residual char formation of adjacent tissues; (ii) distinct time expenditure have strictly limited the use of different laser systems 15. Yet, in the wake of continuous developments in laser technology and an enhanced understanding of laser–tissue interaction, a re‐evaluation of laser osteotomy may be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…1 Excimer laser light provides precise ablation of bone with minimal thermal damage to the surrounding tissue. 2,3 Segas et al 4 demonstrated the efficacy of using excimer lasers for changing the shape of the middle ear ossicles during ear surgery in an experimental model. Scanning electron microscopy of ossicles showed minimal surface damage beyond the laser target site.…”
Section: Introductionmentioning
confidence: 99%